Pelatihan Petani dalam Produksi Pupuk Organik di Desa Tegalgede, Kecamatan Sumbersari, Kabupaten Jember - Rizal Perlambang CNAWP; Uyun Erma Malika (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The increasingly rare and expensive conditions of chemical fertilizers commonly used by farmers have made farmers, including partners, start looking for solutions by using organic fertilizers as a combination. However, a problem has emerged that partners are currently facing, namely related to the production process of organic fertilizers made from goat manure (kohe). The characteristics of goat kohe which takes quite a long time to decompose, means that farmers have to wait approximately one month for the decomposition process, which can then be applied as basic fertilizer on agricultural land. Efforts to accelerate the decomposition process have been carried out by partners, namely by crushing or grinding goat kohe by manually pounding it. This stage requires quite a lot of time and energy, so it is considered inefficient. This is due to the lack of technology adopted in the partner environment. Based on the conditions and problems faced by partners, this activity will offer a solution in the form of goat kohe processing technology as a raw material for organic fertilizer. This community service activity is carried out by providing counseling and training (practice) on how to make organic fertilizer from goat kohe, which is accompanied by direct application of the use of a goat kohe crusher.